2019
DOI: 10.1002/chem.201806042
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Responsive Arylazopyrazole Gelators: From Organic to Aqueous Media and from Supramolecular to Dynamic Covalent Chemistry

Abstract: Versatile photoresponsive gels based on tripodal low molecular weight gelators (LMWGs) are reported. A cyclohexane‐1,3,5‐tricarboxamide (CTA) core provides face‐to‐face hydrogen bonding and a planar conformation, inducing the self‐assembly of supramolecular polymers. The CTA core was substituted with three arylazopyrazole (AAP) arms. AAP is a molecular photoswitch that isomerizes reversibly under alternating UV and green light irradiation. The E isomer of AAP is planar, favoring the self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 99 publications
(161 reference statements)
1
36
0
5
Order By: Relevance
“…Force‐field calculations reveal that the E ‐AAP possesses a planar conformation, which favors π‐π stacking in aqueous media due to aromatic donor‐acceptor interactions of the electron‐rich pyrazolyl and the electron‐poor phenyl ring (Figure 1 a, Figure S1). In contrast, the Z ‐isomer of AAP features a twisted conformation and a higher dipole moment, which impede π‐π stacking in water [24c] . We verified the calculations of the aromatic donor‐acceptor interactions via 2D NOESY (Nuclear Overhauser Effect Spectroscopy) NMR experiments and confirmed that the aromatic donor‐acceptor interactions of the E ‐isomer are distinctly stronger than the ones of the Z ‐isomer (Figure S2).…”
Section: Resultssupporting
confidence: 72%
“…Force‐field calculations reveal that the E ‐AAP possesses a planar conformation, which favors π‐π stacking in aqueous media due to aromatic donor‐acceptor interactions of the electron‐rich pyrazolyl and the electron‐poor phenyl ring (Figure 1 a, Figure S1). In contrast, the Z ‐isomer of AAP features a twisted conformation and a higher dipole moment, which impede π‐π stacking in water [24c] . We verified the calculations of the aromatic donor‐acceptor interactions via 2D NOESY (Nuclear Overhauser Effect Spectroscopy) NMR experiments and confirmed that the aromatic donor‐acceptor interactions of the E ‐isomer are distinctly stronger than the ones of the Z ‐isomer (Figure S2).…”
Section: Resultssupporting
confidence: 72%
“…Host–gest systems of conventional azobenzenes with cyclodextrins have been well‐established, but their potentials are far from fully realized associated with the photoconversion and thermal stability issues. The use of bis‐methylated azopyrazoles has led to an improved system . Here, pzAzo ether was used to develop a new host–guest system.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, arylazopyrazoles have attracted considerable interest because of their synthetic availability and desirable photochemical properties, such as the high thermal stability of the Z isomer and a large band separation between the E and Z isomers, allowing each to be addressed with a high selectivity [3540]. Consequently, arylazopyrazoles have been employed as photoresponsive gelators [41] and adhesives [42] and for controlling antimicrobial response [4344], cell adhesion to surfaces [45], as well as DNA [46] and microtubule [47] self-assembly using light.…”
Section: Introductionmentioning
confidence: 99%